Seasonal Forecast Workshop, in Wote, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Climate information workshop, Wote, Kenya. A workshop to empower farmers to better understand and use probabilistic seasonal climate information. Kafrine, Senegal.